Can AI Truly Assist in Medical Research? A Professional and Academic Perspective - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2023)
The integration of Artificial Intelligence AI into the healthcare ecosystem is no longer a futuristic concept but a present-day reality, particularly within ...
Keywords: Drug Discovery; Digital Health; Diagnostics; Artificial Intelligence; Patient Care